Non-mercaptalbumin is significantly associated with the coronary plaque burden and the severity of coronary artery disease - Chou, Shengpu (Sci Rep, 2021)
Human non-mercaptalbumin (HNA), oxidized form of serum albumin, has been reported as a useful marker in oxidative stress-related diseases; however, few reports have examined the association between HNA and the severity of coronary artery disease (CAD). The present study evaluated whether the HNA fraction is correlated with coronary artery stenosis in 140 patients considered to have a high risk of CAD or who were suspected of having acute coronary syndrome. The severity of CAD was defined by the number of stenotic coronary vessels and a severity score system (the Gensini score). HNA measurements were performed using our newly established high-performance liquid chromatography methodology. The results had shown that HNA was significantly increased in patients with three-vessel disease, compared with those without CAD or with single-vessel disease (p = 0.025), and was positively correlated with the Gensini score (ρ = 0.421, p < 0.001). A multivariate analysis showed that the number of stenotic vessels was an independent and significant factor associated with HNA (ρ = 1.246, p = 0.012). A logistic regression analysis showed that HNA was a strong predictor of multivessel CAD (odds ratio, 1.12; 95% confidence interval, 1.020–1.229; p = 0.017). These findings indicate that the measurement of HNA could be clinically practical for predicting the severity of coronary artery stenosis.